Hepatocellular carcinoma : cellular and molecular mechanisms and novel therapeutic strategies - Aravalli, Rajagopal N. (SpringerBriefs in Cancer Research, 2014)
This book provides up-to-date information on the development and progression of hepatocellular carcinoma (HCC) with a review of the cellular and molecular mechanisms involved in the disease process. Recent research in HCC has led to significant progress in our understanding of the cellular processes and molecular mechanisms that occur during multi-stage events that lead to hepatocarcinogenesis. The emergence of micro RNAs and molecular targeted therapies have added a new dimension in our efforts to combat this deadly disease, Chapters include discussion and evaluation of current intervention strategies and therapeutic options and a focus on the novel approaches that are being pursued, such as micro-RNA based therapies and personalized medicine to treat liver cancer. This book will be of interest to basic and clinical researchers, as well as to drug developers.